Study on Optimal Parameter and Target for Pulsed-Field Ablation of Atrial Fibrillation - Ye, Xuying; Liu, Shangzhong; Yin, Huijuan; He, Qiang; Xue, Zhixiao; Lu, Chengzhi; Su, Siying (Frontiers in Cardiovascular Medicine, 2021)
Pulsed-field ablation (PFA) had potential advantages in atrial fibrillation ablation, and we aim to confirm the optimal parameter and target of PFA for atrial fibrillation. Two ablation modes in vitro of single-cell system (ablation in electrode cup) and monolayer cell system (ablation in inserts with electrode tips) were established to perform PFA for myocardial cell H9C2 and smooth muscle cell A7r5. Ablation effect, calcium ion influx, the expression of Cx45, and surface morphological change were observed. Three Bama minipigs were used to verify the in vivo ablation effect of PFA. In monolayer cell system, H9C2 was significantly sensitive to PFA compared with A7r5, with shrinking of the whole monolayer. The ablation effect of bidirectional pulse was weaker than that of the two mono-polar pulses. Expressed Cx45 proteins were increased in H9C2 but decreased in A7r5 cells. Bidirectional PFA performed on Bama minipigs was able to effectively block electrical activity from the pulmonary vein to the atrium with week muscle contraction, not generating pulmonary vein stenosis. Bidirectional PFA was able to significantly ablate myocardial cells, maintain cell–cell connection, and reduce muscle contraction, which was a kind of optimized PFA strategy for atrial fibrillation.